Real estate's information and volatility links with stock, bond and money markets. (18th May 2018) - Mi, Lin; Hodgson, Allan
Abstract: We examine real estate's information and volatility linkages with stock, bond and money markets. Based on the theory that the volatility of prices directly reflects of the rate at which information flows to the market (Kyle, 1985 ; Ross, 1989 ), we propose that information linkages across markets are revealed in the correlations of their volatilities, rather than correlations of returns. Applying an implied volatility correlation approach and the Generalized Method of Moments (GMM) estimation of Fleming et al . (1998 ) stochastic volatility model, we find strong information and volatility linkages across the four markets.